Proceeding the 9th International Conference on Quality in Research (QiR) Industrial, Manufacturing, Material Engineering, and Management Vol I Depok, 6 - 7 September 2006 - Proceeding... (University of Indonesia Faculty of Engineering, 2006)
tr,1/nr,c.1